1989
DOI: 10.1227/00006123-198911000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Hemangioblastoma of the Spinal Cord: A Report of 18 Cases

Abstract: The cases of 18 patients operated on for hemangioblastoma of the spinal cord were reviewed. There were 11 men and 7 women. (M:F = 1.6:1) and in 15 patients, the onset of spinal symptoms was before the age of 40 years. There were 19 intradural and 2 extradural tumors. The tumor was accompanied by a cyst in 9 patients (50%). There were 6 cases of Lindau's disease, including 3 cases of multiple spinal tumors. Symptoms improved postoperatively in 13 patients, were unchanged in 2, and were aggravated in 3. At the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(36 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…A difference in neurological symptom was not observed between patients harboring sporadic hemangioblastomas and those harboring hemangioblastomas as a manifestation of VHL disease. Regards to the location of the tumor, intramedullary hemangioblastomas were reported as rare cases in previous review 4,18,20,26,28,30,32,[34][35][36] , but in our study intramedullary location (66%) was the most common.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…A difference in neurological symptom was not observed between patients harboring sporadic hemangioblastomas and those harboring hemangioblastomas as a manifestation of VHL disease. Regards to the location of the tumor, intramedullary hemangioblastomas were reported as rare cases in previous review 4,18,20,26,28,30,32,[34][35][36] , but in our study intramedullary location (66%) was the most common.…”
Section: Discussionmentioning
confidence: 48%
“…Hemangioblastomas are vascular tumors that can be found throughout the central nervous system including spinal cord that account for approximately 2% of primary spinal cord tumors 9,18,35) . They are benign neoplasm (World Health Organization Grade I), but can cause significant morbidity and mortality through mass effect according to the intraspinal lesion 20,27) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This multiplicity accounts for the varied natural history of spinal cord hemangioblastomas associated with VHL, complexities in their management and uncertainties associated with longterm functional outcome. 14,18,19 Our study revealed that 66 (46.5%) out of 142 VHL patients examined had spinal cord hemangioblastomas. Although sporadic spinal cord hemangioblastomas are found in approximately 10-20% among all CNS hemangioblastomas, spinal cord hemangioblastoma with VHL is a more common manifestation.…”
Section: Discussionmentioning
confidence: 64%
“…15,18,19 Spinal cord hemangioblastomas may occur sporadically or in association with VHL, which is a multisystem familial cancer syndrome. Approximately two-thirds are sporadic in origin and the other third are associated with VHL.…”
Section: Discussionmentioning
confidence: 99%